Religious diversity in Asia - Borup, Jørn (International Studies in Religion and Society, 2020)
The religious landscape in Asia has long been diverse, with various forms of syncretic traditions and pragmatic practices continuously having been challenged by centrifugal forces of differentiation. This anthology explores representations and managements of religious diversity in Japan, China, South Korea, Vietnam, the Philippines, Indonesia, Sri Lanka, India and diaspora religions originating in these countries, seen through the lenses of history, identity, state, ritual and geography. In addition to presenting empirical cases, the chapters also address theoretical and methodological reflections using Asia as a laboratory for further comparative research of the relevance and use of 'religious diversity'. Religious Diversity in Asia was made possible by a framework grant from the Danish Agency for Science, Technology and Innovation allowing the grant holder (Jørn Borup) and two colleagues (Marianne Q. Fibiger and Lene Kühle) to host a workshop at Aarhus University and to co-arrange workshops in Delhi and Nagoya. We would like to thank professors Arshad Alam and Michiaki Okuyama for hosting these latter workshops at Jawaharlal Nehru University and Nanzan University, and we would like to thank Professor Chong-Suh Kim for the invitation for Jørn Borup to visit Seoul National University. We would also like to extend our gratitude to all the scholars who participated in the workshops and to all the authors we subsequently invited to contribute to our endeavor to create this academically relevant volume.